Enhancing the stiffness of vertical graphene sheets through ion beam irradiation and fluorination. (26th June 2017) - Lin, Chen; Davami, Keivan; Jiang, Yijie; Cortes, John; Munther, Michael; Shaygan, Mehrdad; Ghassemi, Hessam; Robinson, Jeremy T; Turner, Kevin T; Bargatin, Igor
Abstract: Many applications of graphene can benefit from the enhanced mechanical robustness of graphene-based components. We report how the stiffness of vertical graphene (VG) sheets is affected by the introduction of defects and fluorination, both separately and combined. The defects were created using a high-energy ion beam while fluorination was performed in a XeF2 etching system. After ion bombardment alone, the average effective reduced modulus ( E r ), equal to ∼4.9 MPa for the as-grown VG sheets, approximately doubled to ∼10.0 MPa, while fluorination alone almost quadrupled it to ∼18.4 MPa. The maximum average E r of ∼32.4 MPa was achieved by repeatedly applying fluorination and ion bombardment. This increase can be explained by the formation of covalent bonds between the VG sheets due to ion bombardment, as well as the conversion from sp 2 to sp 3 and increased corrugation due to fluorination.